2022
DOI: 10.1111/1365-2435.14036
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐mediated responses to aridity and experimental drought by springtail communities across Europe

Abstract: 1. The capacity to forecast the effects of climate change on biodiversity largely relies on identifying traits capturing mechanistic relationships with the environment through standardized field experiments distributed across relevant spatial scales. The effects of short-term experimental manipulations on local communities may overlap with regional climate gradients that have been operating during longer time periods. However, to the best of our knowledge, there are no studies simultaneously assessing such lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Recent progress in the availability of global trait datasets (Griffith et al, 2023; Pincheira‐Donoso et al, 2023; Tobias et al, 2022) provides the basis for testing long‐standing questions on global biodiversity patterns with trait‐based approaches. Many of the studies included in this Special Focus worked on large spatial scales across elevational (Drag et al, 2023) and latitudinal gradients (Ferrín et al, 2023; Ibarra‐Isassi et al, 2023; Srivastava et al, 2023), or even covered the entire globe (Ali et al, 2023; Crouch & Jablonski, 2023; Pincheira‐Donoso et al, 2023). Importantly, these large‐scale analyses are no longer restricted to vertebrates (Etard et al, 2020), but are now also possible for many invertebrate groups including ants, beetles, springtails and aquatic macroinvertebrates.…”
Section: Question 2 Upscaling Understanding From Small To Large Spati...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent progress in the availability of global trait datasets (Griffith et al, 2023; Pincheira‐Donoso et al, 2023; Tobias et al, 2022) provides the basis for testing long‐standing questions on global biodiversity patterns with trait‐based approaches. Many of the studies included in this Special Focus worked on large spatial scales across elevational (Drag et al, 2023) and latitudinal gradients (Ferrín et al, 2023; Ibarra‐Isassi et al, 2023; Srivastava et al, 2023), or even covered the entire globe (Ali et al, 2023; Crouch & Jablonski, 2023; Pincheira‐Donoso et al, 2023). Importantly, these large‐scale analyses are no longer restricted to vertebrates (Etard et al, 2020), but are now also possible for many invertebrate groups including ants, beetles, springtails and aquatic macroinvertebrates.…”
Section: Question 2 Upscaling Understanding From Small To Large Spati...mentioning
confidence: 99%
“…First, large‐scale studies provide broad environmental gradients and help to detect previously unknown associations between functional traits and environmental conditions. For instance, this has enabled the identification of functional traits mediating springtail responses to aridity and drought (Ferrín et al, 2023) or mechanisms of species sorting according to ant functional traits across forest biomes (Ibarra‐Isassi et al, 2023). Second, and even more important, large‐scale analyses of trait diversity can be used to test macroecological theory (Lamanna et al, 2014) and assembly rules of ecological communities and networks (Marjakangas et al, 2022).…”
Section: Question 2 Upscaling Understanding From Small To Large Spati...mentioning
confidence: 99%
See 2 more Smart Citations
“…Species are expected to seek new habitats when natal habitats deteriorate. Field studies showed that Collembola have a high dispersal ability for new habitats when experiencing dry conditions (e.g., Ferrin et al 2022). Consequently, increasing movement between habitats may save populations from local extinction when patches experience inhospitable environmental conditions.…”
Section: Discussionmentioning
confidence: 99%